Ensuring Sustainable Environment and Development: A Study of Solid Waste Management in the University of Lagos, Nigeria - Bakare , Tewo V. (African Journal of Education,Science and Technology (AJEST), 2018)
Management of waste is vital to environmental sustainability and sustainable development efforts, which are key goals of the sustainable development goals (SDGs). This experimental research examined solid waste management within the University system. It employed a combination of enlightenment and the introduction of a specifically designed bottle-shaped dust-bin to ascertain sorting of solid waste into appropriate containers, to encourage the University residential community’s adherence to the reduce, reuse and recycle (3Rs) approach. The study was conducted using Sensitization Campaigns, Interviews, Observation and the Questionnaire. The research raised five questions and used a combination of qualitative and quantitative techniques for data gathered from 250 residents of the staff living quarters of the University of Lagos, Nigeria. A careful examination and measurement of the contents of existing dustbins revealed that there was up to 75% increase in the adherence rate to recycling after the Campaigns. The various challenges faced were noted and it was emphasized that, in order to bring about environmental sustainability, the driving principle must be sustainable development, and the University system must re-examine its role in leading-by-example to increase its contribution to sustainable development. It is hoped that, if the idea of the self-explanatory bottle-shaped bin is adopted, it can be useful in encouraging proper sorting of garbage. The study finally proposed a model for sustainable development within the University environment and in the society at large that will be responsive to environmental sustainability.